2022
DOI: 10.1116/6.0001857
|View full text |Cite
|
Sign up to set email alerts
|

Study of SnO/ɛ-Ga2O3 pn diodes in planar geometry

Abstract: SnO/[Formula: see text]-Ga2O3 vertical p–n diodes with planar geometry have been fabricated on c-plane Al2O3 and investigated by current–voltage measurements. The effects of the in-plane conduction through the Si-doped [Formula: see text]-Ga2O3 layer on the diode performance and their relevance have been evaluated. A significant series resistance is observed, which shows typical features of the variable range hopping transport observed in Si-doped [Formula: see text]-Ga2O3; this in-plane transport mechanism is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…[29] Nonetheless, the extrinsically doped layers suffered from a limited electron mobility (at room temperature µ ≈ 1 cm 2 V −1 s −1 ) due to a hopping transport mechanism. [28,29] As recently suggested by Kneiß et al [30] and some authors of this work, [31] this could be linked to the nanometric-sized rotational domains representing an effective barrier for the in-plane electronic conduction, i.e., a perturbation in the lateral crystal periodicity comparable to the electrons' mean free path. [29] Therefore, finding synthesis conditions that could at the same time allow the extrinsic doping of the material and a domain size control would represent a major step forward for the understanding of the real κ-Ga 2 O 3 intrinsic material properties, which is in turn fundamental for its breakthrough in the field of new generation electronic devices.…”
Section: Introductionsupporting
confidence: 62%
“…[29] Nonetheless, the extrinsically doped layers suffered from a limited electron mobility (at room temperature µ ≈ 1 cm 2 V −1 s −1 ) due to a hopping transport mechanism. [28,29] As recently suggested by Kneiß et al [30] and some authors of this work, [31] this could be linked to the nanometric-sized rotational domains representing an effective barrier for the in-plane electronic conduction, i.e., a perturbation in the lateral crystal periodicity comparable to the electrons' mean free path. [29] Therefore, finding synthesis conditions that could at the same time allow the extrinsic doping of the material and a domain size control would represent a major step forward for the understanding of the real κ-Ga 2 O 3 intrinsic material properties, which is in turn fundamental for its breakthrough in the field of new generation electronic devices.…”
Section: Introductionsupporting
confidence: 62%
“…The adoption of the correct model associated with a given junction is extremely important, since an inappropriate choice can lead to the wrong determination of the carrier type . For instance, in the case of planar diodes, the series resistance given by the portion of material around the diode junction area has a high impact on the measurements and can drastically affect the estimate of the junction properties . The series resistance can influence the capacitance measurement, which itself can cause large errors in calculation of the doping profile, and built-in potential .…”
Section: Resultsmentioning
confidence: 99%
“…SnO resulted rather polycrystalline, with random in-plane orientation; then, lattice match does not seem to matter. Information about the XRD 2θ–ω scan of the SnO(001)/κ-Ga 2 O 3 diode under study is reported in the Supporting Information of ref , where also more details about the fabrication procedures of the SnO/κ-Ga 2 O 3 diode, its geometrical dimensions, and doping levels of the p- and n-type sides, independently investigated as single layers, are given . Further information about the result of room temperature Raman spectroscopy measurement of the SnO layer is given in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations